Adaptative biological response of aerobic granular sludge to events of single or combined wastewater related stressors - Alves, Marta (2025)
Wastewater comprises various stressors and their individual and combined immediate effects on aerobic granular sludge (AGS) are still underexplored. In this study, the AGS was exposed for 24 hours to wastewater with varying salt concentrations (up to 30 g NaCl L⁻¹) alongside pharmaceuticals (diclofenac, DCF or carbamazepine, CBZ). Differences in extracellular polymeric substances (EPS) production and composition were observed between single and combined stressor exposures. The removal of pharmaceuticals was influenced by the wastewater salinity level and the type of pharmaceutical, with a positive correlation found between the EPS polysaccharides content and the removal efficiency at salinity levels up to 10 g NaCl L⁻¹ . The combination of salinity and pharmaceuticals in wastewater also impacted the AGS bacteriome composition, with the bacteriome of the AGS not-exposed to stressors showing greater similarity to that of AGS exposed to DCF than to that exposed to CBZ, at each wastewater salinity level. Functional profiling suggested that short-term exposure to stressors slightly increased the relative abundance of mismatch repair, cell motility, and homologous recombination functions in the AGS microbiome. Summing up, the stressors impact on AGS bacteriome structure and EPS production varies depending on the pharmaceutical and whether it is combined with salt or not. This study unveiled the immediate AGS response to both single and combined stressors exposure, but a more thoughtful characterization of the bacteriome composition over the early adaptation period to stressors is needed to understand the community succession and to identify key microbial groups.